2011
DOI: 10.1111/j.1462-5822.2011.01646.x
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of a type I interferon pathway in controlling bacterial intracellular infection in mice

Abstract: Defense mechanisms against intracellular bacterial pathogens are incompletely understood. Our study characterizes a type I IFN-dependent cell-autonomous defense pathway directed against Legionella pneumophila, an intracellular model organism and frequent cause of pneumonia. We show that macrophages infected with L. pneumophila produced IFNβ in a STING- and IRF3-dependent manner. Paracrine type I IFNs stimulated up-regulation of IFN-stimulated genes and a cell-autonomous defense pathway acting on replicating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
84
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 66 publications
(128 reference statements)
2
84
0
Order By: Relevance
“…Furthermore, type I IFN-␣ receptor-deficient (IFNAR Ϫ/Ϫ ) macrophages were more permissive to L. pneumophila infection in vitro than were wild-type cells (11). There was no difference in bacterial detection in the lungs when IFNAR2 Ϫ/Ϫ and wild-type mice were compared 48 h after L. pneumophila infection (12), nor was there a difference in lung bacterial burden between wild-type and IFNAR Ϫ/Ϫ mice (13). Despite this, most reports suggest that type I IFN supports cellular resistance to L. pneumophila infection.…”
mentioning
confidence: 87%
“…Furthermore, type I IFN-␣ receptor-deficient (IFNAR Ϫ/Ϫ ) macrophages were more permissive to L. pneumophila infection in vitro than were wild-type cells (11). There was no difference in bacterial detection in the lungs when IFNAR2 Ϫ/Ϫ and wild-type mice were compared 48 h after L. pneumophila infection (12), nor was there a difference in lung bacterial burden between wild-type and IFNAR Ϫ/Ϫ mice (13). Despite this, most reports suggest that type I IFN supports cellular resistance to L. pneumophila infection.…”
mentioning
confidence: 87%
“…The induction of type I IFNs is regulated in part by extracellular sensors, such as TLR4, as well as cytosolic sensors, such as the RNA sensors RIG-I and MDA-5, the DNA sensor cGAS, and the cyclic dinucleotide sensor STING (103)(104)(105). Type I IFNs are elicited during L. pneumophila infection and aid in restricting intracellular bacterial replication (67)(68)(69)(70)(106)(107)(108) Fig. 5A and B).…”
Section: To E) Tlr2mentioning
confidence: 99%
“…Whereas A/J macrophages are permissive for L. pneumophila replication, C57BL/6 macrophages restrict L. pneumophila replication (64). Studying how C57BL/6 macrophages sense and control L. pneumophila infection has allowed for the identification of multiple TLR-and cytosolic PRR-mediated responses involved in this process, such as the NAIP5 inflammasome and the proinflammatory cytokines TNF and type I IFNs (20,(65)(66)(67)(68)(69)(70). Importantly, the activation of cytosolic PRRs involves the sensing of bacterial products, such as flagellin, that are translocated into the host cell cytosol by a functional L. pneumophila Dot/Icm T4SS (71,72).…”
mentioning
confidence: 99%
“…A number of studies demonstrated that bacteria-infected cells produce IFN-b (16)(17)(18)(19)(20)(21)(22)(23)(24). In several infection models, this response has been indicated to depend on cytosolic sensing of bacterial DNA.…”
mentioning
confidence: 99%